Baseline characteristics of arm vessels by preoperative duplex ultrasonography in Korean patients for hemodialysis vascular access. Issue 6 (November 2019) - Cho, Minji; Kim, Jung Sun; Cho, Sungsin; Cho, Won Pyo; Choi, Chanjoong; Ahn, Sanghyun; Min, Sang-il; Ha, Jongwon; Min, Seung-Kee
Background: Preoperative mapping with duplex ultrasonography is crucial for successful vascular access creation for hemodialysis. The aims of this study are to assess the baseline characteristics of arm vessels by preoperative duplex ultrasonography in Korean patients, to find out a preoperative duplex ultrasonography parameter precluding distal arteriovenous fistula creation, to assess the maturation failure rate of arteriovenous fistulas, and to identify associated risk factors. Methods: Preoperative duplex ultrasonography mapping for vascular access creation was done in all patients with end-stage renal diseases during the year 2015. The baseline data of duplex ultrasonography were retrospectively analyzed with follow-up clinical data. Results: A total of 299 end-stage renal disease patients (mean age = 62 years, 62% male) were included. On preoperative duplex ultrasonography, mean diameters of radial artery and cephalic vein at wrist were 2.03 and 2.40 mm in the non-dominant arm and 2.10 and 2.26 mm in the dominant arm, respectively. The most common reason for precluding radial-cephalic arteriovenous fistula at wrist was small-sized cephalic vein. Multivariate logistic regression analysis revealed that the risk factors for inadequate vessels were warfarin treatment, old age (⩾75 years), and peripheral arterial occlusive disease. The rate of arteriovenous fistula maturation failure was 21% and vein diameter <2.5 mm was the only risk factor for arteriovenous fistula maturation failure by multivariate logistic regression analysis. Conclusion: Preoperative duplex ultrasonography evaluation is important to find out inadequate vessels for native arteriovenous fistula and to determine the location of vascular access.